Research on Language Maintenance in China: A CNKI-based Analysis of Mapping Knowledge (European Journal of Behavioral Sciences, 2022)
Based on the studies retrieved from CNKI, the paper explores the development, research status and focus of language maintenance in China with the help of Citespace 5.7. The result shows that (1) despite the late start, the research on language maintenance in China is growing at a stable rate each year, but the number of influential papers is very limited when compared to the total number of papers published; (2) the publications are diversified and the research on language maintenance has drawn attention from and at the same time has gone beyond the minorities language studies circle, but a majority of the papers studied from a macro perspective; (3) the researchers and institutes are widely dispersed, but the most influential ones are very limited, and most work is done independently and teamwork or collaboration is in urgent need; (4) important topics cover endangered language, language protection, minority people and its language, language resource, language diversity, ecology, etc., among which endangered language and language protection have become the research focus with the highest frequency and centrality in recent years.